2011
DOI: 10.3748/wjg.v17.i13.1701
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for premalignant lesions and noninvasive early gastrointestinal cancers

Abstract: ESD is a feasible and safe method for treatment of premalignant lesions and early malignant gastrointestinal epithelial and subepithelial lesions. Successful en bloc and complete resection of lesions yield high cure rates with low recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
9
1
1
Order By: Relevance
“…However, Sakamoto et al [22] and Ohata et al [23] showed that 30 ESD treatments performed independently in the colon were sufficient to obtain an acceptable R0 resection rate, procedure duration, and complication rate. This learning curve was confirmed by studies showing that during the first 25 treatments, the perforation rates were 12-28% [24][25][26][27]. In a European study, Probst et al [15] observed a considerable improvement in resection parameters after two endoscopists each performed 25 procedures as the procedure time decreased from about 200 to 136 min and the proportion of R0 resections increased from 48 to 84.5%.…”
Section: Discussionmentioning
confidence: 87%
“…However, Sakamoto et al [22] and Ohata et al [23] showed that 30 ESD treatments performed independently in the colon were sufficient to obtain an acceptable R0 resection rate, procedure duration, and complication rate. This learning curve was confirmed by studies showing that during the first 25 treatments, the perforation rates were 12-28% [24][25][26][27]. In a European study, Probst et al [15] observed a considerable improvement in resection parameters after two endoscopists each performed 25 procedures as the procedure time decreased from about 200 to 136 min and the proportion of R0 resections increased from 48 to 84.5%.…”
Section: Discussionmentioning
confidence: 87%
“…In Turkey, the early gastric cancer ratio is lower than 10% among all gastric cancer cases and exhibits a parallel trend to other European countries (7,8). Although there are centers in Turkey that successfully perform endoscopic resections for cancer, it is challenging to increase the case volume due to the lack of a screening program for gastric cancer.…”
Section: Management Of Locoregional Diseasementioning
confidence: 99%
“…Endoscopic Submucosal Dissection (ESD) has been shown to be safe for larger lesions and those not amenable to EMR, with high en bloc complete resection rates in experienced centres mostly in Japan. [61][62][63][64] However, it is not widely available in the UK and the majority of evidence for ESD for NETs is from the rectal carcinoid literature. [65][66][67][68][69] Endoscopic resection of nonmetastatic localised lesions <2 cm with ≤6 lesions has been demonstrated to be as effective as surgical resection.…”
Section: Treatment and Surveillancementioning
confidence: 99%